THE EFFECTIVENESS OF USING KAHOOT AS A MEDIA IN TEACHING READING - Ima Chusnul Chotimah; Muhammad Farhan Rafi (E-LINK JOURNAL, 2018)
This research focuses on the use of Kahoot as a media in teching reading for the English Departement students of STKIP PGRI Jombang in academic year 2017/2018. The method used is experimental research with quasi experimental design. There are two classes, they are 2016 B as the experimental class and 2016 A as the control class. The teaching process done in experimental class was using Kahoot as a media, while in 2016 A was using textbook as a media. The instrument used was a test. Before giving the test, the researchers did the content validity and construct validity by conducting the tryout to know the validity and reliability criteria of the test. After knowing all of them are valid and reliable, giving pre test, treatment, and post test was done to get the data of the research. After that, the researchers analyzed the data by using ANCOVA. The result shows that the significant value is 0.02, it is lower than the significant level 0.05. It means that the use of Kahoot as a media for the English Department students of STKIP PGRI Jombang influences their reading skill.